2016
DOI: 10.1111/padm.12248
|View full text |Cite
|
Sign up to set email alerts
|

Does a Public Service Ethic Encourage Ethical Behaviour? Public Service Motivation, Ethical Leadership and the Willingness to Report Ethical Problems

Abstract: This article aims to advance our understanding of and confidence in the relationship between employee public service motivation (PSM) and ethical behaviour by testing the degree to which PSM predicts the ethical behaviour or behavioural intention of government employees. Building on previous research, we argue that government employees with higher PSM are not only more likely to internalize values that support public interests, they also are likely to be concerned less about the potential consequences that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
125
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(135 citation statements)
references
References 63 publications
5
125
1
4
Order By: Relevance
“…Several control variables are also shown to have a statistically significant relationship with fear to voice a dissenting opinion. Consistent with previous studies (Hassan ; Wright et al ), the results show that employees whose immediate supervisor exhibits high levels of ethical leadership have lower levels of fear towards voicing a dissenting opinion. As with previous research (Miceli et al ), gender does not seem to be related to employee voice.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Several control variables are also shown to have a statistically significant relationship with fear to voice a dissenting opinion. Consistent with previous studies (Hassan ; Wright et al ), the results show that employees whose immediate supervisor exhibits high levels of ethical leadership have lower levels of fear towards voicing a dissenting opinion. As with previous research (Miceli et al ), gender does not seem to be related to employee voice.…”
Section: Resultssupporting
confidence: 91%
“…Studying the public sector, Hassan () found a positive relationship between a manager's ethical leadership and their employees’ disposition to voice their opinions. Similarly, Wright et al () found that ethical leadership is associated with higher levels of public service motivation among employees, and that this in turn is tied to a higher propensity among staff to report unethical behaviour.…”
Section: Data Variable Operationalization and Methodsmentioning
confidence: 97%
“…Motivating public employees to work toward desirable ends is considered to be an important but difficult task (Behn, 1995). Inherent organisational and job characteristics such as high level of goal ambiguity (Boardman & Sundquist, 2009) emphasise on altruistic motivation (Perry, Hondeghem, & Wise, 2010), and high expectations for morality (Wright, Hassan, & Park, 2016) rendered public managers to focus on managing by values (Bryson & Bloomberg, 2014). Following a tradition of public ethos (Horton, 2008), this line of thought tries to align public employees' personal values to the organisational values through selection and socialisation to harness the benefits of value congruence (Edwards & Cable, 2009) such as elevated attitudes (Verquer, Beehr, & Wagner, 2003) and performance (Hoffman & Woehr, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to concerns about whether we can hold government accountable for desired policy outcomes, decreasing trust levels also re ect concerns that the actions of public administrators during policy implementation are driven by self-interest rather than the interests of the larger public or community (Wright et al 2016).…”
Section: Trustmentioning
confidence: 99%